2019
DOI: 10.1021/acsnano.9b04757
|View full text |Cite
|
Sign up to set email alerts
|

Setting Carriers Free: Healing Faulty Interfaces Promotes Delocalization and Transport in Nanocrystal Solids

Abstract: Superlattices of epitaxially connected nanocrystals (NCs) are model systems to study electronic and optical properties of NC arrays. Using elemental analysis and structural analysis by in situ X-ray fluorescence and grazing-incidence small-angle scattering, respectively, we show that epitaxial superlattices of PbSe NCs keep their structural integrity up to temperatures of 300 °C; an ideal starting point to assess the effect of gentle thermal annealing on the superlattice properties. We find that annealing such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(69 citation statements)
references
References 48 publications
(90 reference statements)
7
62
0
Order By: Relevance
“…Higher-quality epi-SLs will in turn encourage more in-depth analysis of the tomograms, particularly with regard to disorder across length scales longer than those emphasized in this paper. 30 Finally, we note that improving the tomogram resolution by a factor of two would allow visualization of QD facets and atomic-scale defects such as edge dislocations, 58 thereby providing a comprehensive nearatomistic picture of the 3D structure of these mesoscale QD lms.…”
Section: Resultsmentioning
confidence: 99%
“…Higher-quality epi-SLs will in turn encourage more in-depth analysis of the tomograms, particularly with regard to disorder across length scales longer than those emphasized in this paper. 30 Finally, we note that improving the tomogram resolution by a factor of two would allow visualization of QD facets and atomic-scale defects such as edge dislocations, 58 thereby providing a comprehensive nearatomistic picture of the 3D structure of these mesoscale QD lms.…”
Section: Resultsmentioning
confidence: 99%
“…To minimize the impact of dielectric screening, we analyzed the absolute absorptance of a series of QD superlattices built from PbSe or CdSe QDs. 15 17 Such samples combine a 0D confinement with a 2D geometry, 18 which makes that only minor corrections are needed for the screening of the electromagnetic field (see also Figure 1 ). More precisely, we calculated for the different QD samples the local field factor F , which is the ratio between the external and the local electric field using atomistic dielectric modeling (see Supporting Information S8 ) and found that | F | 2 ranges between 0.4 and 0.8.…”
Section: Monolayer Qd Superlatticesmentioning
confidence: 99%
“…These height differences together with irregularities in the in-plane directions indicate the degree of structural disorder in the superlattice. We assign these imperfections to the size distribution of the building blocks and inhomogeneities in the epitaxial connections of the nanocrystals occurring in the two (001) directions of the rock-salt crystal structure [18,22,36].…”
Section: Methodsmentioning
confidence: 99%